Patrones y problemas de sueño en los niños de la Escuela de Educación Básica Miguel Riofrío - Vélez Elizalde, Jhoseth Samir (2022)
Sleep is a physiological state related to the well-being of various homeostatic systems and functions. Alterations to its structure can develop changes in its patterns and be manifested by sleep problems, however, these are usually underdiagnosed by medical personnel and present variability in its prevalence among different regions. 3 The aim of this study was to characterize sleep problems and sleep patterns of children in a public school. The population of the present study consisted of 113 children in an urban school, mostly male and mixed race between 4 and 7 years of age, to whom a questionnaire of sociodemographic characteristics elaborated by the authors and the Children's Sleep Habits Questionnaire were applied. The overall prevalence of sleep problems was approximately 16%. The main sleep problems were bedtime resistance 22.12%, delayed sleep onset 19.47% and nighttime awakenings 18.58%. Specific problems that affected more than half of the population were: fear of sleeping alone (66.3%), need to sleep in someone else's bed (60.1%), need to have parents in the room to sleep (57.5%), fear of sleeping in the dark (56.6%), restless or restless sleep (54.9%). Finally, the total sleep time was only considered ideal in children aged 6-7 years. Our results highlight the importance of implementing early identification and timely education in children from the first-levels health care system as well as conducting epidemiological studies on a larger scale on a topic that has been little studied locally